Effect of environmrntal disturbances on odonata assemblages along a tropical polluted river - Abdul, Nurul Huda; Md Rawi, Che Salmah; Ahmad, Abu Hassan; Al-Shami,, Salman Abdo (De Gruyter, 2017)
Odonata larvae have been intensively used as bioindicators for freshwater pollution as their community structure closely follow changes in the environment and habitat settings. In this study, 28 taxa of Odonata larvae were collected from three stations (upper, middle and lower) of a polluted river in Malaysia. The upper river basin receives effluents from an oil palm plantation. However, the middle station is presumably contaminated with anthropogenic wastes. The lower station is found to receive polluted discharges from aquaculture outlet. Several environmental parameters of water and sediment were continuously measured during the study. The water parameters showed no significant differences amongst the three stations. The species richness of Odonata was 22, 24 and 20 in the upper, middle and lower stations, respectively. The abundance of Odonata was significantly different among the studied sites. The tolerant damselfly, Pseudagrion sp. (41.22%), and facultative dragonflies, Onychothemis sp. (17.12%), were the most dominant taxa along the river stations. Onychothemis sp. and Paragomphus capricornis were equally important at the upper station [Important Species Index (ISI) 25.3 and 24.2%, respectively]. Pseudagrion sp. only scored an ISI value of 9.7%. Pseudagrion sp., P. capricornis and Onychothemis sp. were dominant in the middle station (ISI: 41.2%, 25.9% and 10.9% respectively), and Pseudagrion sp., Onychothemis sp. and Prodasineura sp. dominated the areas with dense growth of submerged aquatic weeds Hydrilla sp. in the lower station (ISI: 47.9, 24.5 and 13.8%, respectively). On the basis of the variations in larval abundance and ISI values, microhabitats differences partly in response to different types of pollutions entering the water structured the Odonata communities in this river basin.